(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2018)
In the context of expanding community engagement efforts by universities and growing awareness of the past and current impacts of settler-colonialism in Canada, this study explores one Indigenous-settler, community-university partnership. Building on a framework of community-university engagement and decolonization, this case study explores a partnership between Fraser Valley Aboriginal Children and Family Services Society (Xyolhemeylh) and the Division of Health Care Communication at the University of British Columbia (UBC-DHCC). This partnership, called the “Community as Teacher” program, began in 2006 and engages groups of UBC health professional students in three-day cultural summer camps. This qualitative case study draws on analysis of program documents and interviews with Xyolhemeylh and UBC-DHCC participants. The findings of the study are framed within “Four Rs”—relevance, risk-taking, respect, and relationship-building—which extend existing frameworks of Indigenous community-university engagement (Butin, 2010; Kirkness & Barnhardt, 1991). Committed to a foundation of mutual relevance to their missions, both community and university partners undertook risk-taking, based on their respective contexts, in establishing and investing in the relationship. Respect, expressed as working “in a good way,” likewise formed the basis for interpersonal relationship-building. By outlining the findings in relation to these four themes, this study provides a potential framework for practitioners and researchers in Indigenous-university partnerships